Yabancı Dil Olarak Türkçe Öğretimi ile İlgili Hazırlanan Tezlerde Geçen Anahtar Kelimelere Yönelik İçerik Analizi / Content Analysis of the Keywords in the Dissertations on Teaching Turkish as a Foreign Language - Küçük, Serhat; Kaya, Elif (Journal of History Culture and Art Research, 2018)
Abstract The aim of this study is to determine the frequency of usage of the keywords in Master’s and PhD dissertations prepared between 2010-2017 in the field of teaching Turkish as a foreign language. The sample of the study are 223 dissertations including 178 master’s and 45 PhD in total, which are open access in YÖK national dissertation database center and were written between the years 2010-2017. In this study, document analysis method, which is one of the qualitative research methods, was used. As a result of the research, it was concluded that in a total of 39 dissertations, including 36 master’s and 3 PhD, there were no keywords. In the dissertations left, the 102 different keywords were determined. Depending on these different keywords the 13 different subjects in general were determined. These subjects adress the vocabulary, grammar, culture, idioms and proverbs, basic language skills, Common European Framework References for Languages, motivation-anxiety-adaptation, language learning strategies, textbooks, material-play-activity, assessment-evaluation, teacher competences, student autonomy, methods and techniques, Turkish in Turkey and in the world. All keywords mentioned in dissertations were re-coded according to their subjects. The keywords in the dissertations related to basic language skills were coded and provided additionally. The findings shown in the tables and graphs in the study. However, the references of 223 master’s and PhD dissertations were not given in the end of the study in order not to busy too much place in the bibliography of the study. Öz Bu araştırmanın amacı, yabancı dil olarak Türkçe öğretimi alanıyla ilgili 2010-2017 yılları arasında hazırlanmış yüksek lisans ve doktora tezlerindeki anahtar kelimeleri kullanım sıklıklarına göre belirlemektir. Araştırmanın örneklemini, YÖK Tez Merkezinde erişime açık ve 2010-2017 yılları arasında yapılmış olan 178 yüksek lisans ile 45 doktora olmak üzere toplam 223 âdet tez oluşturmaktadır. Çalışmada nitel araştırma yöntemlerinden doküman incelemesi yöntemi kullanılmıştır. Araştırmanın sonucunda; 36 yüksek lisans ve 3 doktora tezi olmak üzere toplam 39 tezde anahtar kelimenin kullanılmadığı görülmüştür. Tezlerde 102 farklı anahtar kelime tespit edilmiştir. Anahtar kelimelerden hareket ederek 'Söz varlığı, dil bilgisi, kültür, deyim ve atasözleri, temel dil becerileri, Avrupa Ortak Çerçeve Programı, motivasyon-kaygı-uyum, dil öğrenme stratejileri, ders kitapları, materyal-oyun-etkinlik, ölçme-değerlendirme, öğretmen yeterlikleri, öğrenci özerkliği, yöntem-teknik, Dünya’da ve Türkiye'de Türkçe’ olmak üzere 13 farklı genel konu alanı belirlenmiştir. Tezlerde geçen tüm anahtar kelimeler, konu alanına göre tekrar kodlanarak bütün bir şekilde gösterilmeye çalışılmıştır. Temel dil becerileriyle ilgili yapılan tez çalışmalarında kullanılan anahtar kelimeler ise ayrıca gösterilmiştir. Elde edilen bulgular tablo ve grafiklerle de gösterilmiştir. Ayrıca 223 âdet yüksek lisans ve doktora tezinin açık künyesi, çalışmanın kaynakçasında fazla yer tutmaması için verilmemiştir.